2010
DOI: 10.1007/s11999-009-1132-z
|View full text |Cite
|
Sign up to set email alerts
|

Results of 32 Allograft-prosthesis Composite Reconstructions of the Proximal Femur

Abstract: The use of allograft-prosthesis composites for reconstruction after bone tumor resection at the proximal femur has generated considerable interest since the mid1980s on the basis that their use would improve function and survival, and restore bone stock. Although functional improvement has been documented, it is unknown whether these composites survive long periods and whether they restore bone stock. We therefore determined long-term allograft-prosthesis composite survival, identified major complications that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 32 publications
0
30
0
8
Order By: Relevance
“…Limb salvage by tumor resection and subsequent reconstruction is the mainstay of treatment for proximal femoral malignancies. Reconstruction with a (modular or custom) proximal femoral endoprosthesis (tumor prosthesis) or an allograft‐prosthesis composite are the two main alternatives . Other surgical options, such as intramedullary nailing without tumor resection, can be used for palliative treatment in bone metastases .…”
Section: Introductionmentioning
confidence: 99%
“…Limb salvage by tumor resection and subsequent reconstruction is the mainstay of treatment for proximal femoral malignancies. Reconstruction with a (modular or custom) proximal femoral endoprosthesis (tumor prosthesis) or an allograft‐prosthesis composite are the two main alternatives . Other surgical options, such as intramedullary nailing without tumor resection, can be used for palliative treatment in bone metastases .…”
Section: Introductionmentioning
confidence: 99%
“…Options for restoring a functional lower extremity after wide resection at this site include megaprostheses [2-4, 6, 14-19, 26-30], osteoarticular allografts [2, 5, 10-12, 21-25, 32], and allograftprosthetic composites (APC) [1,16,17,35], each with unique advantages and disadvantages. Osteoarticular allografts offer the potential benefit of biologic bone union, soft tissue attachment, restoration of bone stock, and preservation of the proximal tibial physis in skeletally immature patients.…”
Section: Introductionmentioning
confidence: 99%
“…They restore bone stock and allow biologic union while providing a stable knee; however, they are technically difficult reconstructions that sacrifice the opposite physis and have some risk of disease transmission, nonunion, and fracture [1,11,16,17,35]. Mankin et al [18] reported good or excellent results in 77% of 98 patients treated with APCs; however, this was an overall rating and results were not reported by anatomic location.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 We aimed to reduce the incidence of aseptic loosening by increasing the effective volume of the cavity of the bone to accommodate a prosthetic stem, and at the same time to increase the possibility of using a standard revision prosthesis if required later.…”
Section: Discussionmentioning
confidence: 99%